Les dynamiques urbaines de Shanghai : trois artères péri-centrales en mutation - Howard Vazquez (EchoGéo)
This article discusses the dynamics of urban, economic and social in Shanghai, from where the socio-morphological evolution of three peri-urban arteries. The peri-central arteries participate fully in the organization of Shanghainese space. Understanding current developments of the Chinese street has a dual mission: to identify, first, the urban dynamics of streets, understanding on the other hand, the social dynamics. Mutations in the streets can actually appreciate how peri-urban arteries evolved since the early 1990’s as part of the broader redefinition of the municipality, and to analyze the dynamics of both social, political and economic.